The Development of Biodiversity Module Using Discovery Learning Based on Local Potential of Wonosobo (Journal of Innovative Science Education, 2020)
A module is a mean of supporting Biology learning in addition to the textbook as a reference. The reference book that is used, still presents theories, concepts, and general examples and does not represent the local environment. Meanwhile, Wonosobo has the potential for interesting biodiverstity to be used in learning. The use of Discovery Learning is suitable to be applied to biodiversity material because it provides opportunities for students to get material through the surrounding environment. The research aims to develop and find out the appropriateness and the effectiveness of biodiversity module using Discovery Learning model on local potential of Wonosobo. The module was developed according to the research and development procedures by Sugiyono (2015). The test sample was taken using a purposive sampling technique. Small-scale test sample was done on 10 students. The large-scale trial design used the pretest-posttest control group design, class X MIPA 1 as a trial class of 32 students and class X MIPA 2 as a control class of 31 students. The results of the T-test obtained a value of 0,000 <Î± which showed a significant difference. The increase in learning outcomes (N-Gain) in the experimental class is 67% in the medium criteria, the achievement of the KKM was 75% of students with an average value of 71.88. The research result shows that the development of biodiversity module using Discovery Learning based on local potential of Wonosobo is appropriate and effective to be used in SMAN 1 Kertek.